Empirical analysis of the impact of technology import on industrial innovation in China: a technology expenditure perspective - Bingqiang Li; Xueru Zu; Min Chen; Jinzhi Li; Guihua Shen; Shan Wang (Journal of Business Economics and Management)
Promoting steady industrial innovation through technology import is an important initiative to accelerate innovation-driven and high-quality economic development in China. In this study, a model of the impact of technology import on industrial innovation is constructed from the perspective of technology expenditure, and empirical analysis is made by employing panel data from 2011 to 2019 in China. There exists obvious regional and industrial differences in the level of technological innovation and the intensity of technology import in China. The econometric results indicate that technology import and industrial innovation are complementary generally, but in the eastern region, as well as the labor- and the technology-intensive industries appear to be substitute. There are obvious regional differences when considering the impact of the interaction items, and the acceleration of technology digestion and absorption is conducive to the improvement of innovation, while that on various industries fail the significant test except for the technology-intensive industry.